Management of Double Impacted Teeth 22 and 23 Combination of Fixed Orthodontics and Surgical Exposure: Penatalaksanaan Impaksi Ganda Gigi 22 dan 23 Kombinasi Ortodontik Cekat dan Surgical Exposure - Lila Muntadir; Ganendra Anugraha; Ervina Restiwulan Winoto; Eddy Heriyanto; Nur Masita Silviana (Academia Open, 2025)
Background: Double impaction of two teeth in the same region specifically tooth 22 and tooth 23 is a rare condition that requires a combined treatment approach involving fixed orthodontics and surgical exposure. Fixed orthodontic treatment is essential to prepare space, guide tooth movement after surgical exposure, prevent root resorption, and correct overall malocclusion. Surgical exposure is performed to expose the tooth crown, preserve the alveolar bone, avoid root exposure, and facilitate the attachment of buttons and ligatures. Impacted teeth can affect the stomatognathic system, facial growth, and aesthetics. The maxillary incisors and canines play a critical role in occlusion, masticatory function, and facial aesthetics, thus requiring appropriate management. Objective: To describe the management of a double impaction case in the anterior left maxillary region of a 19-year-old female patient using a combined approach of fixed orthodontic and surgical treatment. Methods: The patient underwent fixed orthodontic treatment and sequential extraction of premolars 14 and 24 to create space for the eruption of the impacted teeth and to correct the midline before surgical exposure. Post-surgical exposure, orthodontic treatment was continued to guide both teeth into proper alignment within the dental arch. Results: Teeth 22 and 23 successfully erupted with good occlusion. The patient's masticatory function and facial aesthetics improved over a 2-year period following surgical exposure. Conclusion: Fixed orthodontic treatment combined with surgical exposure is an effective strategy for managing double impaction of anterior teeth in the left maxillary region, considering the position of the crowns, tooth inclination, and root apex morphology of the impacted teeth. Highlights: Double impaction of teeth 22 and 23 is rare and affects function and aesthetics. Combined surgical and orthodontic treatment effectively guided tooth eruption. Treatment restored occlusion, midline, and facial aesthetics over 2 years. Keywords: Anterior tooth double impaction, surgical exposure, fixed orthodontic treatment